2015
DOI: 10.1016/j.jchf.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Further Peripheral Vascular Dysfunction in Heart Failure Patients With a Continuous-Flow Left Ventricular Assist Device

Abstract: Background Peripheral endothelial function is recognized to be impaired in patients with heart failure with reduced ejection fraction (HFrEF), but the peripheral vascular effects of continuous-flow left ventricular assist device (LVAD) implantation, now employed as either a bridge-to-transplantation or as a destination therapy, remain unclear. Using flow-mediated vasodilation (FMD) and reactive hyperemia (RH), this study aimed to provide greater insight into LVAD-induced changes in peripheral vascular function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 46 publications
2
64
0
Order By: Relevance
“…6), which means the series type LVAD may promote the benefit of swirling flow. These changes maybe improve the complications caused by conventional LVAD support, such as peripheral vascular dysfunction [33] and impaired vascular compliance [34]. In addition, from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6), which means the series type LVAD may promote the benefit of swirling flow. These changes maybe improve the complications caused by conventional LVAD support, such as peripheral vascular dysfunction [33] and impaired vascular compliance [34]. In addition, from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that CF support is associated with increased peripheral vascular reactivity, which is caused by impaired reactivity of both the endothelial and smooth muscle cell layers due to a decrease in bioavailability and response to NO. Witman et al also used FMD and reactive hyperemia to evaluate the vascular function of subjects with heart failure ( n = 32), patients on CF LVAD support ( n = 20), or healthy controls ( n = 16). These authors showed that the %FMD/shear rate was significantly reduced in the CF LVAD group compared to all the other groups and that the %FMD/shear rate significantly correlated with pulsatility index.…”
Section: Chronic Effects Of Continuous‐flow Supportmentioning
confidence: 99%
“…HFrEF = Heart Failure with Reduced Ejection Fraction. Reproduced from Witman, et al, [41] with permission.…”
Section: Figurementioning
confidence: 99%
“…These changes do not appear to be manifest at the end-organ level, however, as evidenced by a lack of difference in the vasculature with regard to perivascular infiltrates, intravascular infiltrates, wall thickness, thrombosis, endothelial cell swelling, vessel wall necrosis, or perivascular fibrosis [40]. However, larger vessels, such as the brachial artery, have been shown to have reduced flow-mediated vasodilation in patients with continuous flow LVADs compared to control patients without LVADs [41]. These differences could also be observed with regard to changes in vessel diameter (Figure 2).…”
Section: Introductionmentioning
confidence: 99%